PENGENDALIAN KECEPATAN MOTOR SINKRON MAGNET PERMANEN (MSMP) TIPE INTERIOR DIATAS KECEPATAN DASAR - Muhammad Bachtiar (Foristek, 2013)
This paper presents a method to control Permanent Magnet Synchronous Motor (PMSM) at high speed above the based speed. To control PMSM from zero speed up to base speed, the armature voltage of the motor may be varied up to maximumvoltage allowed of the inverter used. In this region the stator voltage will increases with the increases of motor speed reaches the based speed, motor voltage cannot increase anymore because of saturation and consequently motor speed cannot be increase more highly. In order motor to control the motor above base speed, it is can be done by weakening the field flux of the rotor. As the rotor made of permanent magnet, then filed weakening control cannot be done directly. The control of field-weakening effect is done by controlling stator current vector of direct axix, which is variable with speed